2008
DOI: 10.1111/j.1365-2958.2008.06200.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant‐dependent switching between reversible and sacrificial oxidation pathways for Bacillus subtilis OhrR

Abstract: SummaryThe Bacillus subtilis OhrR protein functions as a transcriptional repressor of the inducible peroxidase, OhrA. Derepression is mediated by the organicperoxide selective oxidation of an active site cysteine (C15). In the presence of cumene hydroperoxide (CHP), oxidation of OhrR leads to a sulphenic acid intermediate which reacts to form either a mixeddisulphide or a protein sulphenamide. These inactive forms of OhrR can be reactivated by thiol-disulphide exchange reactions allowing restoration of repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 29 publications
2
41
1
Order By: Relevance
“…6); however, addition of 1 mM DTT could not reestablish OhrRC121S DNA binding activity. The results are consistent with the recent hypothesis that the conserved cysteine at the C terminus plays a role in prevention of the overoxidation of the redox-sensing cysteine (33,34). The overoxidized forms of cysteine are sulfinic acid and sulfonic acid, which cannot be reduced by DTT (17).…”
Section: Discussionsupporting
confidence: 81%
“…6); however, addition of 1 mM DTT could not reestablish OhrRC121S DNA binding activity. The results are consistent with the recent hypothesis that the conserved cysteine at the C terminus plays a role in prevention of the overoxidation of the redox-sensing cysteine (33,34). The overoxidized forms of cysteine are sulfinic acid and sulfonic acid, which cannot be reduced by DTT (17).…”
Section: Discussionsupporting
confidence: 81%
“…Most of the transcription factors involved in the oxidative stress response use reactive cysteines to control their activity, often forming a reversible disulfide bond (29,30). In contrast, although, the peroxide-sensing regulator OhrR of B. subtilis undergoes oxidation either to a reversible cysteine sulfenic acid intermediate or to cysteine sulfinic and sulfonic acid derivatives (31), modifications that are irreversible (i.e., sacrificial) in bacteria. Our in vitro analyses showed that FixK 2 might select between the reversible and irreversible modes of inactivation, depending on the nature of the oxidant.…”
Section: Two Modes Of Fixk2mentioning
confidence: 99%
“…The C15 sulfenic acid can either rapidly form a mixed disulfide with a cellular free thiol (i.e., bacillithiol, a recently identified 398-Da thiol) or react with the amino group of an adjacent amino acid residue to form a cyclic sulfenamide (17,68). Mixed disulfide and protein sulfenamide formation is reversible since DNA binding activity of these derivatives of OhrR was able to be recovered in vitro by reduction in the presence of dithiothreitol (DTT) (68,102). Irreversible inactivation of OhrR results when the C15 sulfenic acid is further oxidized to either a sulfinic (C15-SOOH) or sulfonic (C15-SO 3 H) acid, a process which occurs either in cells exposed to highly efficient inducers, like linoleic acid hydroperoxide, or in organic peroxideexposed cells already undergoing disulfide stress (68).…”
Section: Ohrrmentioning
confidence: 99%
“…For example, OhrR proteins of B. subtilis and Xanthomonas campestris are more sensitive to complex organic peroxides, such as linoleic acid hydroperoxide, while Agrobacterium tumefaciens OhrR preferentially senses less-complex organic peroxides like cumene hydroperoxide (57,85,102).…”
Section: Ohrrmentioning
confidence: 99%